Colorimetry as a petroleum toxicity and biodegradation screening technique - Bidoia, Ederio Dino [UNESP]; Montagnolli, Renato Nallin [UNESP]; Lopes, Paulo Renato Matos [UNESP] (My University, 2014)
Treatment of hydrocarbon-contaminated environments is still a great challenge today. Oily residues present in refinery separation systems waste or even the accumulation in the storage tanks has been an increasing issue. There are many places contaminated with oil that may affect public health or the balance of local ecosystems, compromising the future economic development of affected regions. Several factors control biodegradation intensity of oil and its toxicity to organisms in the environment. Waste oil have a wide variety of hazardous components with high toxicity. Petroleum components such as nitrogen and sulfur are highly toxic when metabolized, primarily in form of ammonia and hydrogen sulfide. Biodegradation is a dynamic process: its environment conditions, microbiota and metabolites are all variables as the process advances. The conditions for biodegradation processes depends on many factors such as electron acceptors like oxygen, nitrate, sulfate or carbon dioxide that allow biodegradation to be complete. On this basis, it is possible to develop toxicity and biodegradation colorimetric assays that provide important information on the effects of environmental pollution on organisms. In contrast to other chemical analyzes, redox dyes can easily detect the effects of multiple contaminants, byproducts and metabolites during bioremediation processes. Resazurin is an indicator that changes from blue to red during bacterial respiration. The cell growth inhibition may indicate toxicity and it can be determined by methods based on the reduction of redox indicators. The same principle can be used in the analysis of biodegradation of oil in microbial community using other redox indicator, 2,6- dichlorophenol-indophenol, whose color change when reduced. When the indicator is oxidized its color is blue, and when reduced is colorless. The color change is due to the change in the structure of the molecule window to receive electrons resulting from reactions in biodegradation processes. Thus, using the colorimetry is possible to analyze different microcosms according to their capacity of biodegradation and their response to toxicity of various petroleum products. All the measurements take into account the time required for complete discoloration as an indicator of biodegradation of the oil or inhibition of cells for toxicity. Toxicity of the oils varies with time and may cause growth inhibition and mortality in organisms. Furthermore, different profiles for different discoloration are observed to occur in each substance degraded. In addition, comparison with the phyto-toxicity data is also important to provide conclusive data on the biodegradation generated oil metabolites affecting the growth of plants in soil. The biotransformation of oils can cause an increase toxicity of these substances and intermediates toxic oils may be formed over the test duration and thereby increasing the toxicity of the oil. The assessment of acute toxicity have shown that the volatile aromatic hydrocarbons as compounds that influence on toxicity. Added to this, low molecular weight hydrocarbons as present in gasoline and diesel exhibit intense acute toxic effect, mainly due to their high solubility and presence of more volatile molecules with ability to penetrate cells and alter and damage cellular structures.
Keywords: Bacillus subtilis; DCPIP; Phyto-toxicity; Rezazurin